2015
DOI: 10.1165/rcmb.2014-0300oc
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Channel 3 Channels in the Activation and Migration of Human Blood Eosinophils in Allergic Asthma

Abstract: Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is responsible for respiratory burst in immune cells. Chloride channel 3 (CLC3) has been linked to the respiratory burst in eosinophils and neutrophils. The effect of cytokines and the involvement of CLC3 in the regulation of NADPH-dependent oxidative stress and on cytokine-mediated migration of eosinophils are not known. Human peripheral blood eosinophils were isolated from healthy individuals and from individuals with asthma by negative selection. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
(56 reference statements)
2
16
0
Order By: Relevance
“…Quantification data are presented as the mean ± SEM in relative units of this work, however, is that these changes induced by Ang II are significantly inhibited by ClC-3 knockdown and further potentiated by ClC-3 overexpression, suggesting the requirement of ClC-3 for NADPH oxidase-derived ROS generation in endothelial cells. Over the past decade, the correlation between ClC-3 and intracellular ROS generation has been suggested in several studies, in which ClC-3 has been shown to be involved in Noxdependent oxidative stress in vascular smooth muscle cells, neutrophils, eosinophils and endothelial progenitor cells [10][11][12][13]. The present study, to our knowledge, is the first to provide evidence that Ang II-induced Nox activity and signaling require ClC-3 in endothelial cells.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Quantification data are presented as the mean ± SEM in relative units of this work, however, is that these changes induced by Ang II are significantly inhibited by ClC-3 knockdown and further potentiated by ClC-3 overexpression, suggesting the requirement of ClC-3 for NADPH oxidase-derived ROS generation in endothelial cells. Over the past decade, the correlation between ClC-3 and intracellular ROS generation has been suggested in several studies, in which ClC-3 has been shown to be involved in Noxdependent oxidative stress in vascular smooth muscle cells, neutrophils, eosinophils and endothelial progenitor cells [10][11][12][13]. The present study, to our knowledge, is the first to provide evidence that Ang II-induced Nox activity and signaling require ClC-3 in endothelial cells.…”
Section: Discussionsupporting
confidence: 63%
“…Deficiency in ClC-3 inhibits Nox1-derived ROS production induced by cytokines in the endosomes of vascular smooth muscle cells [11]. The dependence of NADPH oxidase activity on ClC-3 was also recently described in human blood eosinophils [12]. Consistent with these findings, our recent study showed that a lack of ClC-3 inhibited angiotensin II (Ang II)induced endothelial progenitor cell apoptosis by suppressing ROS generation from NADPH oxidase [13].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Allergen exposure drives oxidative stress by causing airway epithelium and smooth muscle cells to produce ROS, particularly O 2 -, through activation of NADPH oxidase (4,5). Other sources of ROS include inflammatory cells like eosinophils (6), neutrophils (7), and monocytes/macrophages (8). Asthmatics have increased hydrogen peroxide (9) and nitric oxide (10) as exhaled gases supporting the role of oxidative stress in asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the initiation of apoptosis has been reported as an alternative role to respiration for eosinophil mitochondria . As eosinophils produce large amounts of nicotinamide adenine dinucleotide phosphate oxidase (NOX)2‐dependent extracellular reactive oxygen species (ROS) upon activation, it is commonly thought that oxygen consumption by eosinophils supports ROS production rather than oxidative phosphorylation (OXPHOS). Contrary to this, human eosinophils are sensitive to oligomycin (mitochondrial ATP synthase inhibitor), suggesting that in addition to glycolysis, mitochondria can indeed contribute, at least in part, to ATP production .…”
Section: Introductionmentioning
confidence: 99%